2017
DOI: 10.1177/0263395717724295
|View full text |Cite
|
Sign up to set email alerts
|

Growing into politics? The development of adolescents’ views on democracy over time

Abstract: This study focuses on how views on democracy develop during adolescence. A total of 40 Dutch adolescents were interviewed in their second and fourth year of secondary education. The study shows that the interviewed adolescents do become more familiar with politics but do not develop more nuanced views towards democracy. As the adolescents age, a one-dimensional perspective on democracy becomes more apparent. In the interviewees' perspective, democracy increasingly equals majority rule. Other aspects, such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Citizenship is inextricably connected to democracy (Geijsel, Ledoux, Reumerman, & Ten Dam, 2012;Hattam, 2016;Miller, 2000;Nieuwelink, Dekker, & Ten Dam, 2018). Citizenship and democracy are connected to the political domain but, especially for adolescents, also to other spheres of life, such as the household, voluntary associations and schools (Nieuwelink, Ten Dam, Geijsel, & Dekker, 2017;Sapiro, 2004). In this article, we focus on three aspects of democracy and citizenship.…”
Section: Developing Attitudes Towards Democratic Citizenshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Citizenship is inextricably connected to democracy (Geijsel, Ledoux, Reumerman, & Ten Dam, 2012;Hattam, 2016;Miller, 2000;Nieuwelink, Dekker, & Ten Dam, 2018). Citizenship and democracy are connected to the political domain but, especially for adolescents, also to other spheres of life, such as the household, voluntary associations and schools (Nieuwelink, Ten Dam, Geijsel, & Dekker, 2017;Sapiro, 2004). In this article, we focus on three aspects of democracy and citizenship.…”
Section: Developing Attitudes Towards Democratic Citizenshipmentioning
confidence: 99%
“…Adolescent political participation is also rather limited (Elchardus, Herbots, & Spruyt, 2013;Munniksma et al, 2017). Adolescents are, therefore, more positively oriented towards democracy and democratic values than they are towards formal political institutions (Nieuwelink et al, 2016a(Nieuwelink et al, , 2017Schulz et al, 2010). Furthermore, young people have different orientations towards democratic citizenship.…”
Section: Developing Attitudes Towards Democratic Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation
“…They also emphasized the strength of the voice of majority and only some recognized the voice of the minorities in decision making (cf. Nieuwelink et al., ). This opinion was very much present in context of attitudes toward immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research among adolescents has indicated that the understanding of democracy that emphasizes individual rights and freedoms, democratic representation, and civic equality prevails (De Groot et al., ; Flanagan, ; Flanagan, Gallay, Gill, Gallay, & Nti, ; Husfeldt & Nikolova, ). Longitudinal study of adolescents in the Netherlands showed that during adolescence, young people become more familiar with politics (Nieuwelink, Dam, Geijsel, & Dekker, ). Nevertheless, they do not necessary develop more complex views on democratic decision‐making.…”
Section: Introductionmentioning
confidence: 99%